Ku chrześcijańskim korzeniom Europy. Znaczenie nawrócenia cesarza Konstantyna dla Kościoła, dla Cesarstwa Rzymskiego, dla Europy - Grzywaczewski, Józef (Vox Patrum, 2014)
The article is consecrated to Constantine’s conversion and to its consequences for the Church, for the Roman Empire and for Europe. There is a general opinion that, even if his attachment to Christianity was not very mature, he worked for the Christian religion during all his life. He has taken many decisions on behalf of the Church; he protected her against the Donatists in Africa. His position towards the Arian heresy was not very clear. He did not pay attention to the dogmatic formulas, but especially to those solutions which guaranteed peace among people. Surely, the emperor once introduced into the Church, remained there as her protector and head. The society was accustomed the emperor’s position as pontifex maximus. Bishops did not protested against his involving into ecclesiastic matters because he worked on their behalf. The effect of Constantine’s attitude was: the Christianization of the Roman Empire and the connection of the Church to the State. In later centuries such an alliance of the altar with the throne was boring for the Church. It is said that every privilege has to be paid. The Roman Empire was collapsed in the end of the fifth century, but its heritage remained in Europe. Charlemagne, cooperating with Pope Leon III, tried to restore the Roman Empire as a Christian State, but he failed to do it. Surely, by his support for schools and studies, he contributed to the European culture. The idea of the Sacrum Imperium Romanum appeared again in the times of Otto I, and especially of Otto III. Such an idea was not possible to be put into practice. The Roman Empire has never been restored, but many of its elements were assimilated by the Church and by medieval Europe. There are to be noticed in all European countries in our time.